2020
DOI: 10.1002/cnma.201900640
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Role of Mn Doping on the Bulk Structure Stability and Interfacial Stability of Ni‐Rich Layered Oxide

Abstract: Nickel‐rich layered oxides have developed into appealing cathode materials for lithium‐ion batteries in recent years for the sake of high energy density and low cost, but they suffer from severe capacity deterioration during long‐term cycling. Herein, Mn‐doped nickel‐rich Li(Ni0.88Co0.09Al0.03)1‐δMnδO2 (δ=0, 0.01, 0.02) cathode materials with a nanoscale NixMn1−xO‐type pillar layer are synthesized using a facile high‐shear dry mixing and high‐temperature calcination process in this study. The as‐fabricated M0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Currently, surface coating and ion doping are the two main strategies to solve the above problems. Coating, as a common surface modification method, shows a positive effect on structural stability, side reaction inhibition, and the optimization of electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, surface coating and ion doping are the two main strategies to solve the above problems. Coating, as a common surface modification method, shows a positive effect on structural stability, side reaction inhibition, and the optimization of electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performances of four samples (NC, V O -NC-1, V O -NC-2, and V O -NC-3) were measured using CR2025 coin cells, and the influence of elevated annealing temperature and time on electrochemical performances is explored as well (Figure ). Meanwhile, the performance is also compared with those reported in other literature studies as shown in Table S4. Figure a shows the initial charge–discharge profiles of four samples, and the discharge capacities of modified cathode materials declined slightly at elevated annealing temperature and time. Although the NC sample obtains highest initial discharge capacity, its cycling performance is inferior as shown in Figure b, exhibiting only 155.3 mAh·g –1 (74.31% capacity retention) after 100 cycles at 0.2 C rate.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Recently, researchers have been attempting to improve the structural stability of nickel-rich cathodes via replacing transition metals with atoms of different elements. According to reports, various atoms (Na, Al, Ti, Mn, Y, Zr, Gd, F, and B) have been used to dope the nickel-rich layered cathode materials, which led to a great improvement in the electrochemical performance of the materials [10,13,19,[32][33][34][35][36]. Furthermore, Sun et al have demonstrated that W-doping can surmount the problem in LiNiO 2 with inherent structure instability and significantly improve its cycle performance and thermal properties without reducing its capacity [37].…”
Section: Introductionmentioning
confidence: 99%